Effect of chromium and iron compounds on the hydraulic properties of portland cement - Singh V.K.; Singh R.K.; Khattri S.D. (My University, 2025)
The effects of addition of Cr2O3, CrO3, Cr(OH)3, Fe2O3, and Fe(OH)3 on the properties of cement have been studied using 0.5 to 5.0 per cent of additives by weight of cement. The variation in setting time, strength, heat of hydration of cement with different percentage of additives were investigated. Chemical interactions occur between the additives and hydrating cement particles and as a result change in colour of the cement along with variation of other properties were observed. X-ray diffraction data have shown the presence of new phases in the cement samples with additives. © 1998 Taylor and Francis Group, LLC.